Pengembangan Video Pembelajaran Berbasis Aplikasi Kinemaster Pada Pembelajaran Tema 6 Subtema 3 di SDN Sumorame - Kurniawati, Riekke; Ardiyah, Miftakul (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2023)
The retention of the in a development on the background is based on the problems facing learners want to create a media platform video based. This development research prompts to develop learning video by using application kinemaster on theme (hot and moving) subtheme 3 (spreader kalor of life) learning 1 a class 5 defence at SDN Sumorame methods used in this technology is research develop by using the ADDIE model belonging to Dick and Carry which is carried out through 3 stages, namely analysis including needs analysis and material analysis, design with a frame of reference in the from of (a) setting learning tools (b) making concept designs (c) preparation of questions and answer, development by collecting video-based learning media materials or materials such as (a) selection of illustrative images that match the material (b) typig text on the material (c) inserting supporting videos (d) inserting instruments (e) then proceeding with the help of supporting applications needed, without going through the implementation and evaluation stages due to the pandemic which cannot be carried out face to face bit online. The results of the research from material experts showed that the percentage results were 71 % and 80 %. So it can be concluded that the video learning based application kinemaster on theme 6 â€œhot and movingâ€ subtheme 3 â€œspreader kalor of lifeâ€ learning 1 grade 5 at SDN Sumorame is declared â€œvalidâ€ to be used.